An outback oasis: the ecological importance of bilby burrows - Dawson, S.J.; Broussard, L.; Adams, P.J.; Moseby, K.E.; Waddington, K.I.; Kobryn, H.T.; Bateman, Bill; Fleming, P.A. (WILEY, 2019)
Ecosystem engineers are species that have a role in creating and maintaining certain habitat traits that are important for other species. Burrowing species do this by creating subterranean refugia from predation and thermal extremes, but also providing foraging opportunities through soil movement and by increasing local landscape heterogeneity. In this study, we used camera traps to monitor the burrows of greater bilbies (Macrotis lagotis), a vulnerable Australian marsupial, in an area subject to frequent disturbance by fire. We tested the hypothesis that bilby burrows provide refuge for other species and therefore their presence increases biodiversity. In total, 45 taxa – 22 bird, 16 reptile and 7 mammal taxa – were recorded interacting with 127 burrows across 7 sites. Species richness was greater at burrows compared with vegetation away from burrows, while abundance was no different. There was no difference in species assemblage for bilby burrows that were actively maintained by bilbies compared with abandoned burrows, although there was more activity at bilby maintained burrows. A wildfire allowed us to test the ad hoc hypothesis that the use of bilby burrows was greater when vegetation cover was removed by fire. We recorded significant differences in species assemblage interacting with burrows after fire, although overall species richness and abundance did not change. The response of individual species was variable; for example, burrows provide a refuge for smaller species (such as mice and small reptiles), and may therefore protect them from the effects of fire. Where they persist, bilbies provide an important ecosystem engineering service, as their burrows support a broad range of species. Further reduction in the distribution of the bilby is therefore likely to have a flow-on effect on biodiversity, impacting species that use their burrows for refuge.